(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The article highlights current issues of classification of the world’s languages, and reviews the results of modern philological research on this issue. The classifications of domestic and foreign linguists have been studied. Definitions are given to the classifications of world languages and their comparative analysis is carried out.